2020
DOI: 10.1016/j.dnarep.2020.102785
|View full text |Cite
|
Sign up to set email alerts
|

Cancer type-dependent correlations between TP53 mutations and antitumor immunity

Abstract: Many studies have shown that TP53 mutations play a negative role in antitumor immunity. However, a few studies reported that TP53 mutations could promote antitumor immunity. To explain these contradictory findings, we analyzed five cancer cohorts from The Cancer Genome Atlas (TCGA) project. We found that TP53-mutated cancers had significantly higher levels of antitumor immune signatures than TP53-wildtype cancers in breast invasive carcinoma (BRCA) and lung adenocarcinoma (LUAD). In contrast, TP53-mutated canc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
84
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(96 citation statements)
references
References 27 publications
11
84
1
Order By: Relevance
“…The results for the dataset TCGA-LUAD revealed that NAL, TMB and smoking history correlated significantly with the NTRK3 mutation status but that the age, sex, stage, race, and ethnicity did not. Interestingly, we also found that the mutation rate of Tp53 was higher in patients with NTRK3-MT, consistent with prior reports that Tp53 mutations are associated with enhanced antitumor immunity in LUAD (Li et al, 2020). Overall, these results highlight a potential role of NTRK3-MT as a predictive biomarker for ICI treatment.…”
Section: Correlations Between Ntrk3 Mutations and Clinical Characterisupporting
confidence: 91%
See 1 more Smart Citation
“…The results for the dataset TCGA-LUAD revealed that NAL, TMB and smoking history correlated significantly with the NTRK3 mutation status but that the age, sex, stage, race, and ethnicity did not. Interestingly, we also found that the mutation rate of Tp53 was higher in patients with NTRK3-MT, consistent with prior reports that Tp53 mutations are associated with enhanced antitumor immunity in LUAD (Li et al, 2020). Overall, these results highlight a potential role of NTRK3-MT as a predictive biomarker for ICI treatment.…”
Section: Correlations Between Ntrk3 Mutations and Clinical Characterisupporting
confidence: 91%
“…For example, clinical studies have confirmed that ICIs do not enhance OS in NSCLC patients with EGFR mutations; in other words, patients with EGFR mutations do not respond well to immunotherapy (Akbay et al, 2013;McGranahan et al, 2016;Lin et al, 2019). A study from Li et al showed that the correlation between Tp53 mutations and tumor immunity differs among tumor types and that the Tp53 mutation status may be a negative predictor for response to ICIs in these cancers (Li et al, 2020). KRAS comutations and TET1 mutations have been demonstrated to be novel predictors for ICI response in different cancer types (Skoulidis et al, 2015;Wu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between TP53 and immune signature has been confirmed in other recent work by Li et al, indicating the connections between TP53 mutations and anticancer immunity as a consequence of the effect of the altered TMB and tumor aneuploidy level due to TP53 mutations on tumor immunity [71]. In particular, they discovered that, in HNSC, tumor aneuploidy level more strongly affected antitumor immunity than TMB [71]. It is necessary to keep in mind that early mutations in TP53, a frequent finding in leukoplakia as well as in head and neck carcinoma, are related to a copy number genomic instability [72].…”
Section: Mutational Load and Immunology: Should These Factors Be Analsupporting
confidence: 68%
“…They found that TP53 mutations were present with reduced immune signatures while HRAS mutations were related to increased immune signatures in HNSCC [70]. The relationship between TP53 and immune signature has been confirmed in other recent work by Li et al, indicating the connections between TP53 mutations and anticancer immunity as a consequence of the effect of the altered TMB and tumor aneuploidy level due to TP53 mutations on tumor immunity [71]. In particular, they discovered that, in HNSC, tumor aneuploidy level more strongly affected antitumor immunity than TMB [71].…”
Section: Mutational Load and Immunology: Should These Factors Be Analmentioning
confidence: 53%
See 1 more Smart Citation